The impact of workplace violence on job burnout among Chinese correctional officers: the chain mediating effects of stress and insomnia - Jizhi Wang; Ying Huang; Siyuan Wang; Zheng Zhang; Yuqiong He; Xiaoping Wang; Huijuan Guo (BMC, 2024)
Abstract Background The risk of workplace violence and job burnout among Chinese correctional officers is high. Stress and insomnia may influence the relationship between workplace violence and job burnout; however, this influence has been rarely studied. This study aimed to explore the effect of workplace violence on job burnout among Chinese correctional officers and to assess the contribution of stress and insomnia to this effect. Methods In this study, the workplace violence scale, the Assens insomnia scale, the 21-item Depression Anxiety Stress Scale, and the Maslach Burnout Inventory-General Survey scale were used to assess the workplace violence, insomnia, stress, and job burnout experienced by the 472 correctional officers, respectively. Results The results showed that (1) workplace violence was significantly and positively predictive of job burnout, (2) workplace violence affected job burnout through the mediation of stress, (3) workplace violence affected job burnout through the mediation of insomnia, and (4) stress and insomnia played fully interlocking mediating roles in the effect of workplace violence on job burnout. Conclusion Stress and insomnia may play a full mediating role in the relationship between workplace violence and job burnout. This suggested that correctional officers may take measures to reduce stress and improve insomnia, thereby reducing their job burnout. Further research may focus on the development of effective interventions to reduce stress and improve insomnia among correctional officers.